Evidence-based cross validation for acoustic power transmission for a novel treatment system. Issue 3 (4th May 2017) - Mihcin, Senay; Strehlow, Jan; Demedts, Daniel; Schwenke, Michael; Levy, Yoav; Melzer, Andreas
Abstract: Introduction: The novel Trans-Fusimo Treatment System (TTS) is designed to control Magnetic Resonance guided Focused Ultrasound (MRgFUS) therapy to ablate liver tumours under respiratory motion. It is crucial to deliver the acoustic power within tolerance limits for effective liver tumour treatment via MRgFUS. Before application in a clinical setting, evidence of reproducibility and reliability is a must for safe practice. Materials and methods: The TTS software delivers the acoustic power via ExAblate-2100 Conformal Bone System (CBS) transducer. A built-in quality assurance application was developed to measure the force values, using a novel protocol to measure the efficiency for the electrical power values of 100 and 150W for 6s of sonication. This procedure was repeated 30 times by two independent users against the clinically approved ExAblate-2100 CBS for cross-validation. Results: Both systems proved to deliver the power within the accepted efficiency levels (70–90%). Two sample t -tests were used to assess the differences in force values between the ExAblate-2100 CBS and the TTS ( p > 0.05). Bland-Altman plots were used to demonstrate the limits of agreement between the two systems falling within the 10% limits of agreement. Two sample t -tests indicated that TTS does not have user dependency ( p > 0.05). Conclusions: The TTS software proved to deliver the acoustic power without exceeding the safety levels. Results provide evidence as a part of ISO13485 regulations for CE marking purposes. The developed methodology could be utilised as a part of quality assurance system in clinical settings; when the TTS is used in clinical practice.